Modeling of rheological dependencies of the process of oil material extruding - A. V. Gukasyan; E. P. Koshevoy; V. S. Kosachev; A. A. Shkhalyakhov; Z. A. Meretukov (Новые технологии, 2019)
The aim of the research is to develop rheological dependences of the oil material during extrusion and to simulate viscosity of the material when producing vegetable oil by pressing in an extruder during the flow of a plastically deformable porous medium. Methods of mathematical modeling of structural models of viscosity have been used to describe both non-linear plastic and pseudo-plastic flows. The technique is based on the fact that the viscoplastic properties of the Bingham flow are taken into account. An approximation of the flow equations has been presented within the Bingham rheological model, taking into account the experimentally established effect of hydrostatic pressure on the shear stress of the sunflower pulp entering the extruder. Plastic viscosity remains almost constant.The effective viscosity has been considered as consisting of two components: the plastic viscosity, that corresponds to the Newtonian fluid viscosity, and the structural viscosity, which characterizes the shear resistance caused by the tendency of the solid particles contained in the Bingham fluid to form a structure. As a result of the studies, the influence of the main parameters of the extrusion process on the effective viscosity of the oil material has been assessed. The need to use the most theoretically substantiated Bingham equation has been substantiated, which allows you to determine the effective viscosity over a sufficiently large interval of shear rates in the extruder channel.As a result, rheological models of the shear flow have been determined that describe both plastic and pseudo plastic flows with fairly good accuracy.